2007
DOI: 10.1002/rcm.3010
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of psychotropic phenylalkylamine derivatives in human hair by gas chromatography/mass spectrometry

Abstract: A gas chromatography/mass spectrometric (GC/MS) method was developed and validated for the determination of thirteen psychotropic phenylalkylamine derivatives (amphetamine; AP, phentermine; PT, methamphamine; MA, cathinone; Khat, methcathinone; MCAT, fenfluramine; FFA, desmethylselegiline; DSEL, 3,4-methylenedioxyamphetamine; MDA, 3,4-methylenedioxymethamphetamine; MDMA, 3,4-methylenedioxyethylamphetamine; MDEA, norketamine; NKT, mescaline; MES, 4-bromo-2,5-dimethoxyphenethylamine; 2CB) in human hair. Hair sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 31 publications
0
54
0
Order By: Relevance
“…The abuse of phentermine has previously been reported using human hair [1,7], but that of phendimetrazine was first proved by hair analysis in the current study. Most phendimetrazine abusers were multidrug abusers of phendimetrazine, phentermine, and/or methamphetamine (13 of 14 subjects).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The abuse of phentermine has previously been reported using human hair [1,7], but that of phendimetrazine was first proved by hair analysis in the current study. Most phendimetrazine abusers were multidrug abusers of phendimetrazine, phentermine, and/or methamphetamine (13 of 14 subjects).…”
Section: Discussionmentioning
confidence: 66%
“…For example, hair analysis demonstrated that opioid analgesics and benzodiazepines were illegally abused especially by medical professionals, who can easily obtain those drugs [5,6]. Chronic use of some anorectic agents was also proved by hair analysis [1,3,7].…”
Section: Introductionmentioning
confidence: 98%
“…The application of the described methodology allows the simultaneous detection and quantification of the mentioned compounds in nail samples. The simultaneous detection and quantification of several kinds of abused drugs is advantageous to toxicologists who are frequently confronted with limited sample size and detection of multiple drug use (Kim et al, 2007).…”
Section: Application Of the Methods To The Fingernails Of Suspected Drmentioning
confidence: 99%
“…Acylation of the NH or NH 2 functional group present in all these compounds with either PFAA or HFAA lowers the basicity of the amine, which allows other fragmentation pathways to occur, resulting in clear distinguishing MS spectra. Comparable approaches using TFAA for derivatization of phenylalkylamines such as methamphetamine (31) and others including phenteramine, cathinone, and mescaline (32) or ketamines (33) and subsequent GC/MS have been reported. Human metabolism of ephedrines including ephedrine and phenylpropanolamine was generally found to be low based on TFAA derivatization and GC/MS results.…”
Section: Acylationmentioning
confidence: 99%